Text and interpretation - Modarressi Tabataba'i, Hossein. ([Cambridge, Massachusetts])
451 sayfa
Keywords: “Text and Interpretation: Imam Jaʻfar al-Ṣādiq and his Legacy in Islamic Law examines the main characteristics of the legal thought of Imam Jaʻfar al-Ṣādiq, a preeminent religious scholar jurist of Medina in the first half of the second century of the Muslim calendar (mid-eighth century CE). Numerous works in different languages have appeared over the past half century to introduce this school of Islamic law and its history, legal theory, and substance in contexts of Shi'i law. While previous literature has focused on the current status of the school in its developed and expanded form, this book presents an intellectual history of how the school began. The Jaʻfari school emerged within the general legal discourse of late-Umayyad and early- Abbasid periods, but was known to differ in certain approaches from the other main legal schools of this time. Namely, the Jaʻfari school expanded the tools for legal interpretation generally and contracts specifically, to a degree unmatched by any of its counterparts in the Muslim legal tradition. In addition to sketching the origins of the school, the book examines Jaʻfar al-Ṣādiq's interpretive approach through detailing his position on a number of specific questions, as well as the legal canons, presumptions, and other interpretive tools he adopted.“ --